Análise de viabilidade econômica da microgeração distribuída fotovoltaica no Brasil - PEREIRA, Tiago de Oliveira (2018)
The growing demand for electricity, in association with the need to diversify the energetic matrix with the insertion of renewable sources, has aroused interest in the possibility of generating its own electricity from the sun, a renewable source that has been explored exponentially in recent years. In Brazil, specifically, there are massive conditions that further favor the use of this type of source, among which stand out: good solarimetric conditions, increasing evolution of electric energy tariffs and legal security, provided by a strong regulation. In this context, this dissertation has as main goal an analysis of the economic viability of the distributed microgeneration photovoltaic, from the perspective of the residential consumer. The analysis was conducted to the 27 Brazilian capitals, considering the predefined assumptions in the six scenarios analyzed and making use of the following merit figures of the financial analysis: Internal Rate of Return (IRR), Net Present Value (NPV), and Payback return on investment. In addition to the classic merit figures, a sensitivity analysis was performed to evaluate the performance of merit figures as a function of the variations of the variables that have a strong correlation with them. The application of this method resulted in the realization that there is economic feasibility in this type of investment for all the Brazilian capital cities.